Serotonin and substance P coexist in neurons of the rat's central nervous system - Chan-Palay, Victoria (1978)
5-Hydroxytryptamine (serotonin)-containing neurons in the rat's medullary raphe and interfascicularis hypoglossi cell groups were identified by means of autoradiography following prolonged intraventricular administration of 5-hydroxy[(3)H]tryptamine, fluorescence histochemistry for the demonstration of endogenous 5-hydroxytryptamine, and microspectrofluorimetric analysis of excitation and emission spectra. Immunocytochemical methods (the unlabeled primary antibody—peroxidase antiperoxidase and indirect immunofluorescence methods) were applied with antisera to substance P in order to localize immunoreactivity in these medullary neurons. It was demonstrated that the raphe nuclei and the interfascicularis hypoglossi nucleus are heterogeneous cell groups that contain: (i) Neurons that display both an uptake—storage capacity for 5-hydroxy[(3)H]tryptamine and a formaldehyde-induced fluorescence with spectral characteristics identical to those of the 5-hydroxytryptamine fluorophor. These cells exhibit high to low fluorescence intensities without detectable substance P-like immunoreactivity. (ii) Neurons with various 5-hydroxytryptamine fluorescence intensities and intense to low degrees of substance P-like immunoreactivity. (iii) Neurons with various degrees of substance P-like immunoreactivity without detectable 5-hydroxytryptamine fluorescence or 5-hydroxy[(3)H]tryptamine uptake and storage capacity. These results indicate that some neurons contain high or low levels of only 5-hydroxytryptamine or substance P, whereas other neurons contain both 5-hydroxytryptamine and substance P in various proportions. The present findings demonstrate the presence of two putative transmitters, a biogenic amine and a polypeptide, within the same neuron in the mammalian central nervous system.